Análisis de la cinética del secado de cacao nacional ecuatoriano y mejorado ccn-51. - Chiguano Cuchiparte, Willian Patricio (2023)
Due to the inaccuracies in the procedure of the drying kinetics of national cocoa and CCN-51 that limits the analysis of the behavior models of the moisture content as a function of time and temperature and thus help to control the effects within the quality of cocoa beans, an analysis of the drying kinetics of Ecuadorian National and Improved CCN-51 cocoa is made. To carry out the process, the following equipment was used: a grain dehydrator with a capacity of 15 kg, with which drying tests were carried out from a temperature of 40°C to 80°C, a grain moisture meter which indicates moisture from 1% to 40%, which will indicate the final and initial moisture percentage of the grains, a digital precision scale with measurement from 0.01g to 600g in which weight measurements were made for each sample in the nine regimes temperature from 40ºC to 80ºC with a total of 10 samples and a total of 15 cocoa beans.